Detection and attribution of hydrological changes in different climatic and geomorphic regions of China - Liu, Huan; Jia, Yangwen; Su, Huidong; Niu, Cunwen; Wang, Jianhua; Gan, Yongde; Hu, Peng; Yang, Qin (Frontiers in Earth Science, 2023)
Through large-scale hydrological simulation, understanding the impact of different climatic and geomorphic conditions on hydrological variables is valuable for water and land management. However, the related study is still a challenge due to strong environmental diversity in large scale region. The physically-based, national-scale hydrological model in China was developed and validated, which considered the spatial heterogeneity of climatic and geomorphic conditions. Using the model, hydrological differences during the period 1956–2020 in 21 representative basins located in nine climatic zones and four geomorphic regions were quantified. Results showed that: 1) mean annual precipitation was strongly positively correlated with mean actual evapotranspiration, and both increased gradually from north to south. Interestingly, as annual precipitation increases, precipitation tended to be more evenly distributed. In recent decades, the northern river basins have been warming and drying, while the Heihe River basin and the cold northeast regions were under climatic warming and wetting; 2) the spatial distribution of streamflow was consistent with precipitation, but their trends were different. In cold regions affected by frozen soil, the streamflow tended to increase. On the contrary, the basins located in the Warm Temperate Zone with intense human activities and fragile ecosystem had a significant decrease in natural streamflow. As for the streamflow components, the frozen soil and karst structures contributed to the increase of the baseflow index (BFI); 3) The streamflow increase or reduction in 86% of the basins was dominated by climate change, as the contribution rate varied from 51.4% to 95.7%. Affected by the Grain to Green Programme, the streamflow of the Weihe River basin reduced significantly while the BFI increased. However, the reduction of forest, grassland and wetland areas dominated streamflow increase in the Huaihe, and Hulan River basins, and the rates were 65.3% and 66.1%, respectively.